2016
DOI: 10.1186/s13018-016-0351-8
|View full text |Cite
|
Sign up to set email alerts
|

Wound drains in posterior spinal surgery: a meta-analysis

Abstract: BackgroundThe use of drains following posterior spinal surgery is controversial. Thus, the aim of this meta-analysis was to review the advantages and adverse effects of closed suction drainage systems in posterior spinal surgery.MethodsAll randomized and non-randomized controlled trials comparing the use of closed suction drainage with no drainage in posterior spinal surgery were sought in PubMed, Medicine, Embase, and other Internet databases. All of the literature was searched and assessed by two independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 21 publications
1
22
0
2
Order By: Relevance
“…Our results are also limited by the lack of postoperative wound drainage data. It has been demonstrated that drainage affects wound dressing soilage, infection rate, and transfusion risk; however, whereas intraoperative blood loss was meticulously noted in the surgical and anesthesia chart, postoperative registration relied on the attending nurse or physician to note the information in the medical chart. We found that this reporting was inconsistent and deemed that the data would be biased, because the patients with high drainage production would be more likely to have drainage information noted in their chart.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are also limited by the lack of postoperative wound drainage data. It has been demonstrated that drainage affects wound dressing soilage, infection rate, and transfusion risk; however, whereas intraoperative blood loss was meticulously noted in the surgical and anesthesia chart, postoperative registration relied on the attending nurse or physician to note the information in the medical chart. We found that this reporting was inconsistent and deemed that the data would be biased, because the patients with high drainage production would be more likely to have drainage information noted in their chart.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study with the use of MRI showed a significantly lower size and incidence of haematomas on first postoperative day by closed suction drainage systems, however without significant difference in the clinical outcome at 6 months follow-up 50 . Neither the clinical studies found a significant difference concerning postoperative infection rates, wound dehiscence, blood loss or epidural haematomas between patients with or without closed drainage after a non-complex lumbar surgery 48,49,51 . The dressing saturation was higher in patients without drainage 60 .…”
Section: Wound Drainagementioning
confidence: 88%
“…The first ones are responsible for increased SSI rates and are not recommended, whereas the usefulness and the infection risk of the closed suction drainage are controversial 1 . It is known that the formation of postoperative haematomas can increase the SSI rate, as haematomas provide an excellent culture medium for bacteria 48 , increase potentially the incision tension and the spinal cord compression and finally can delay the wound healing 49 . A clinical study with the use of MRI showed a significantly lower size and incidence of haematomas on first postoperative day by closed suction drainage systems, however without significant difference in the clinical outcome at 6 months follow-up 50 .…”
Section: Wound Drainagementioning
confidence: 99%
See 1 more Smart Citation
“…Acil durumlarda kullanılmak üzere kolay ulaşılabilen en az iki tane nontravmatik özellikte klemp hazır bulundurulmalıdır (1, 9-11, 14-17, 21-25). Dren seviyesi aksi durum belirtilmedikçe hasta yatağından aşağıda tutulur eğer hastada lomber drenaj varsa dren bel seviyesinde, EVD'si var ise dren transdüseri foromen monro hizasında tutulmalıdır (5,9,20,21,24,(26)(27)(28). Drenlerin aktif şekilde işlev görmesi için tıkanıklıkların önlenmesi, negatif basınç ortamının sürdürülmesi gerekmektedir.…”
Section: Introductionunclassified